THE IMPLEMENTATION OF HALAL TOURISM IN STARE MIASTO (OLD TOWN) IN THE VIEW OF INTERNATIONAL TOURISTS, ACCEPTANCE AND REJECTION? - Miroslaw Nalazek; Herman Supriadi; Irwan Rahadi (STKIP Persada Khatulistiwa Sintang, 2023)
This research is a quantitative descriptive research that consists of fifty samples. The sample respondens were chosen from several countries. they were chosen randomly and have visited Old Town. Old town is chosen because of its popularity. The data collection used was questionnaires which are shared in two ways (online and offline). Then the questionnaires were collected and tabulated to find the percentage of respondents’ acceptance and rejection to the implementation of Halal tourism in Old Town (Stare Miasto). Due tot to the implementation of Halal tourism in Old Town (Stare Miasto) according to the result percentage of all respondents results from the respondents agree to the implementation of Halal tourism in Old Town with half of the percentage. Though some percentages also are neutral and disagree to the implementation with more than one four of the percentage. Thus, the implementation of Halal tourism in Poland is accepted by tourists.